(untitled) (Journal of the College of Basic Education, 2026)
In this research paper, the researchers explored artificial intelligence as an innovative tool in the design of contemporary interior spaces. AI technologies are a powerful tool for improving planning and design processes, analyzing data, and enhancing the efficiency of interior designers. Furthermore, AI technologies foster innovation and creativity by providing innovative solutions. Exploring modern design ideas, the research problem was embodied in the following question: ((What are the capabilities of artificial intelligence as an innovative tool in providing new design solutions for interior spaces?) Therefore, the aim of the research was to reveal artificial intelligence techniques as an innovative tool in creating functional and aesthetically pleasing interior spaces in contemporary interior design. The first chapter included identifying the research problem and the need for it The first chapter defines its literary and scientific terms, while the second chapter includes a detailed explanation of the theoretical framework adopted by the two researchers, consisting of two sections: the first is the use of artificial intelligence in managing the design process, and the second section is artificial intelligence techniques as innovative tools in developing skills in interior design. Through these discussions, the results were reviewed, summarizing the theoretical material of the three discussions, followed by the conclusions reached by the researcher from studying contemporary interior spaces in museums, and then recommendations and suggestions for future research were presented.